Inherited and acquired immunodeficiencies underlying tuberculosis in childhood. Issue 1 (March 2015) - Boisson‐Dupuis, Stéphanie; Bustamante, Jacinta; El‐Baghdadi, Jamila; Camcioglu, Yildiz; Parvaneh, Nima; El Azbaoui, Safaa; Agader, Aomar; Hassani, Amal; El Hafidi, Naima; Mrani, Nidal Alaoui; Jouhadi, Zineb; Ailal, Fatima; et al.
Summary: Tuberculosis (TB), caused by Mycobacterium tuberculosis ( M.tb ) and a few related mycobacteria, is a devastating disease, killing more than a million individuals per year worldwide. However, its pathogenesis remains largely elusive, as only a small proportion of infected individuals develop clinical disease either during primary infection or during reactivation from latency or secondary infection. Subacute, hematogenous, and extrapulmonary disease tends to be more frequent in infants, children, and teenagers than in adults. Life‐threatening primary TB of childhood can result from known acquired or inherited immunodeficiencies, although the vast majority of cases remain unexplained. We review here the conditions conferring a predisposition to childhood clinical diseases caused by mycobacteria, including not only M.tb but also weakly virulent mycobacteria, such as BCG vaccines and environmental mycobacteria. Infections with weakly virulent mycobacteria are much rarer than TB, but the inherited and acquired immunodeficiencies underlying these infections are much better known. Their study has also provided genetic and immunological insights into childhood TB, as illustrated by the discovery of single‐gene inborn errors of IFN‐γ immunity underlying severe cases of TB. Novel findings are expected from ongoing and future human genetic studies of childhood TB in countries that combine a high proportion of consanguineous marriages, a high incidence of TB, and an excellent clinical care, such as Iran, Morocco, and Turkey.